BRD4 inhibition regulates MAPK, NF‐κB signals, and autophagy to suppress MMP‐13 expression in diabetic intervertebral disc degeneration. Issue 10 (22nd July 2019) - Wang, Jianle; Hu, Jianing; Chen, Ximiao; Huang, Chongan; Lin, Jialiang; Shao, Zhenxuan; Gu, Mingbao; Wu, Yaosen; Tian, Naifeng; Gao, Weiyang; Zhou, Yifei; Wang, Xiangyang; et al.
ABSTRACT: Diabetes mellitus may lead to intervertebral disc degeneration (IVDD). Matrix metalloproteinase‐13 (MMP‐13) is one of the major catabolic factors in extracellular matrix (ECM) metabolism of nucleus pulposus cells (NPCs) and contributes to diabetic IVDD. Bromodomain‐containing protein 4 (BRD4) is a member of the bromodomain and extraterminal protein family and is implicated in chronic inflammation. Here, we report that the expression of BRD4 and MMP‐13 was elevated in diabetic nucleus pulposus tissues as well as in advanced glycation end products (AGEs)‐treated NPCs; also, the regulatory effect of BRD4 on MMP‐13 was studied. We found that MMP‐13 was regulated by MAPK and NF‐κB signaling as well as autophagy in AGEs‐treated NPCs. Next, we explored the role of BRD4 in regulation of MAPK, NF‐κB signaling, and autophagy. The results showed that BRD4 is the upstream regulator of all of these 3 factors, and inhibition of BRD4 may suppress MAPK and NF‐κB signaling while activating autophagy in AGEs‐treated NPCs. Finally, we demonstrated that BRD4 inhibition may suppress MMP‐13 expression in diabetic NPCs in vitro as well as in vivo; meanwhile, it may preserve ECM in diabetic rats. Our study demonstrates that inhibition of BRD4 may suppress MAPK and NF‐κB signaling and activate autophagy to suppress MMP‐13 expression in diabetic IVDD, and diabetic IVDD may be compromised by BRD4 inhibitors.—Wang, J., Hu, J., Chen, X., Huang, C., Lin, J., Shao, Z., Gu, M., Wu, Y., Tian, N., Gao, W., Zhou, Y., Wang, X., Zhang, X. BRD4 inhibition regulates MAPK, NF‐κB signals, and autophagy to suppress MMP‐13 expression in diabetic intervertebral disc degeneration. FASEB J. 33, 11555–11566 (2019). www.fasebj.org